Assessing the resilience of human systems: a critical evaluation of universal and contextual resilience variables. Issue 2 (4th May 2019) - Wilson, Geoff A.; Wilson, Olivia J.
ABSTRACT: This study analyses the use of contextual and universal variables to assess the resilience of human systems. The article examines the terms 'contextual' and 'universal' in relation to resilience variables, how widely accepted different variables are as indicators of resilience, and the extent to which variables can be classified using these conceptual terms. The article analyses how the 'direction' of a variable indicating either resilience or vulnerability can be assessed and argues that often the same variable can be interpreted differently for the resilience of a human system, depending on the context of the system under investigation and the positionality of the researcher. The study informs future resilience research by providing a clearer understanding of the role and status of different variables in relation to measuring and understanding the different domains of resilience in different spatial and research contexts, and invites researchers to think more reflexively about their interpretations of resilience variables.